PRAGMATIZM FALSAFASI ASOSIDA TALABALARNING AMALIY FIKRLAShINI ShAKLLANTIRISh USULLARI - Seytnazarov, S.; Kamalov, M. (SCIENCE and SOCIETY, 2025)
This article analyzes the methodology of forming practical thinking in the educational process based on the philosophy of pragmatism. The ideas of pragmatism are aimed at connecting students' theoretical knowledge with practical activity, developing useful skills in everyday life, as well as making the educational process effective by achieving practical results.
Keywords: pragmatism; education; practical thinking; methodology; student; activity